Implementation of Domestic Market Obligations on Nickel and Bauxite in Indonesia Under International Trade Regime - Adam, Bani; Ahamat, Haniff; Yahanan, Annalisa (Lex Scientia Law Review, 2023)
Increasing global economic activity has resulted in raising demand on nickel and bauxite ores for manufacturing industries. Foremost demand on the raw materials is consistently increasing for production of friendly environment products, such as battery of electric vehicles (EV). The production of EV battery potentially increases particularly as global transformation to reduce GHG Emissions which cover developed and developing countries. This current situation leads export restrictions on nickel and bauxite to developed countries which purpose for domestic stockpile in developing countries, such as Indonesia. Meanwhile, the measures is supposed to violate Article XI.2(a) GATT 1994 which it is applied without temporary period and there is no essentialness circumstance to implement the restrictions. This emphasized on review opportunities for Indonesia to take into force alternative measures which is consistent with the GATT 1994 provisions. The research is conducted based on legal review with refer to GATT 1994 provisions and Indonesia legal provisions. Based on the review, the researchers find that implementation of Domestic Market Obligations are an exact alternative measure to safeguard domestic stockpile without extremely suffer disruption for global demand. The alternative measures grant balancing allocation between global and domestic demand which could be adjusted regularly according to the further situation faced by the country.